INDUSTRY POLICY EFFECTS ON NAMIBIA'S ECONOMIC GROWTH - Emilia Landa Shikomba; Elizabeth Elias; Sirorat Ruttanawijit (Economic Review)
This paper investigates a relationship between economic growth and industrial policy. The methodology employed in this work is the Autoregressive Distributed Lag (ARDL) Model. In addition, the bound cointegration test and Error Correction Model were conducted (ECM). This research estimated the economy of Namibia wherein the industrial policy is narrow and appears to be the second sector contributing to economic growth. The results indicate a significant positive relationship between industrial policy and economic growth. The government may seek to create a favorable business climate and subsidize private firms as well as to reform the labor market and use low-cost technologies to produce products and maintain sustainable economic growth. An action-designed industrial policy will strive to promote manufacturing activities and increase economic growth.